2021
DOI: 10.1016/j.envint.2021.106523
|View full text |Cite
|
Sign up to set email alerts
|

Early-life environmental exposure determinants of child behavior in Europe: A longitudinal, population-based study

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 56 publications
5
43
0
Order By: Relevance
“…As known exposures impacting PSD are still limited and no major advances in the field have been observed recently, agnostic exposure-wide analytical approaches that take into account of inter-correlation may provide further understanding of other, so far, unknown factors that also cover other domains of the exposome such as internal (e.g., inflammation) and external (e.g., chemical, lifestyle, psycho-social) correlates (13). In this regard, similar to previous studies in other phenotypes such as HIV (46), diabetes (47), depression (48), and childhood behavior (49), our research group is currently conducting a systematic exposomewide investigation of correlates of psychosis expression in the UK Biobank.…”
Section: Future Directionssupporting
confidence: 63%
“…As known exposures impacting PSD are still limited and no major advances in the field have been observed recently, agnostic exposure-wide analytical approaches that take into account of inter-correlation may provide further understanding of other, so far, unknown factors that also cover other domains of the exposome such as internal (e.g., inflammation) and external (e.g., chemical, lifestyle, psycho-social) correlates (13). In this regard, similar to previous studies in other phenotypes such as HIV (46), diabetes (47), depression (48), and childhood behavior (49), our research group is currently conducting a systematic exposomewide investigation of correlates of psychosis expression in the UK Biobank.…”
Section: Future Directionssupporting
confidence: 63%
“…More recently, we published a HELIX paper using the same exposome and sub-sample, but in relation to ADHD symptoms and externalizing and internalizing problems based on Child Behavior Check List (CBCL). We observed several prenatal environmental contaminants (indoor air pollution and smoking) and child lifestyle habits (diet, sleep and family social capital) were associated with behavioural problems in children ( Maitre et al, 2021 ). One of the strengths in this previous study on behavioural problems and in our study here on cognition, is that we systematically analysed a much larger range of exposure biomarkers in blood and urine to determine the internal levels in the model, and, we analysed prenatal and childhood exposure variables.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of childhood global developmental [83], internalizing behaviour [84] and neurobehavioral and attention-deficit hyperactivity disorder (ADHD) [85][86][87] outcomes and childhood air pollutant exposure were also published in 2021. ADHD has been explored on many occasions with mixed results; recent longitudinal research supports a mediating role of air pollution in the observed beneficial relation between increasing childhood availability of environmental greenspace and ADHD diagnosis [88].…”
Section: Neurodevelopmental Child and Adolescent Mental Healthmentioning
confidence: 99%